Conservação pós-colheita de melões inteiros e minimamente processados - Morgado, Cristiane Maria Ascari [UNESP] (2013)
This work aimed to determine the influence of refrigeration and controlled atmosphere on quality and postharvest conservation of whole and minimally processed net melons ‘Louis’. Furthermore, the effect of heat treatment associated with the use of active modified atmosphere was evaluated in the conservation of ‘Charentais’ melons minimally processed. In the first experiment, ‘Louis’ melons were stored at 3 °C, 6 ºC, 9 ºC and 22 ºC, 80% RH, to establish the best storage temperature. In the second experiment, the fruits were stored at 6 °C (80% RH) under controlled atmosphere in concentrations of 2%, 7%, 12% and 21% O2, to determine the appropriate concentration of O2 for their conservation. In the third experiment, the melons were stored in controlled atmosphere with 5%, 10%, 15% and 20% CO2 combined with 2% O2, at 6 ºC and 80% RH. In the fourth experiment, the melons were stored under controlled atmosphere (2% O2 and 20% CO2), 6 ºC. The minimal processing was made twice, the first being the fruit immediately upon arrival to the laboratory and the second after 14 days of storage under controlled atmosphere. The fruits and minimally processed products were analyzed for color and firmness, soluble solids and titratable acidity content, pectin (soluble and total), sugars (soluble and reducers), as well as the activity of enzymes peroxidase (POD), polyphenoloxidase (PPO), polygalacturonase (PG) and pectinmethylesterase (PME). They were also analyzed as fresh weight loss, respiratory activity (2nd and 4th experiments) and sensory analysis (experiment 4). In the fifth experiment whole ‘Charentais’ melons were immersed in hot water (50 ºC for 30 min) before being subjected to minimal processing. The cubes were submitted under active modified atmosphere (2-3% O2 and 7-8% CO2), packed with oriented polypropylene film (OPP) or polylactic acid film (PLA) and stored at 6 ºC for ...